PENERAPAN STRATEGI PEMBELAJARAN EKSPOSITORI PADA MATERI GERAK MELINGKAR SISWA KELAS X SMA NEGERI 1 PANGEAN - Ningsih, Elpi Suryati; Irianti, Mitri; Nor, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThe purpose of this research is to know student’s learning cognitive result of the grade X in SMA N 1 Pangean between learning strategies expository and conventional learning in the pith matter of circular motion. The kind of research is Pre-Experimental Designs with research design Intact Group Comparison, where both classes were tested for normality and homogeneity of data and both groups showed that these classes have a homogeneous variance, obtained by using a sweepstakes technique class X1 as a class experiment with Implementation of learning strategies expository and class X2 is a class that has been choose as control class with conventional learning. The research instrument is result test of study. Collecting data is done with giving a test of study’s result after studied. The refinery data is done by descriptive statistics. The research findings : student ability in class with implementation of learning strategies expository is 77%, whereas student ability in class with conventional learning is 70%. Thus implementation of learning strategies expository is effective in increasing cognitive student’s learning of class X SMA N 1 Pangean.Key-Words: Students Learning Cognitive Result, learning strategies expository, circular motion.* Mahasiswa